2019
DOI: 10.1177/0038026119875325
|View full text |Cite
|
Sign up to set email alerts
|

Defiance labour and reflexive complicity: Illusio and gendered marginalisation in DIY punk scenes

Abstract: Since punk emerged in the 1970s as a music genre and subculture it has gained significant academic attention. Punk as a concept now alludes to specific places or scenes, and has been established as a general anti-establishment attitude, as well as an anti-consumerist disposition, with a need to do-it-yourself (DIY). Drawing upon ethnographic and interview data from the east coast of Australia, this article analyses struggles that occur within punk spaces where women and queer identifying punks negotiate histor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…These nuances between self-reflexivity and broader social processes can be explained with the notion of hermeneutic reflexivity, a recognition that reflexivity involves the embodied interpretation of experiences in time and place and stresses how subjectivity informs the orientation of reflexivity (Lash, 1994). For example, Sharp and Threadgold (2019) have shown how gendered privilege can be ignored by men seeking to assert their feminist credentials-a practice they call "reflexive complicity." In this way, it can be argued that reflexivity needs to be understood in the shared practices of agents involved in knowledge (or ignorance) production (Adkins, 2003).…”
Section: Is Reflexive Modernization the Solution?mentioning
confidence: 99%
“…These nuances between self-reflexivity and broader social processes can be explained with the notion of hermeneutic reflexivity, a recognition that reflexivity involves the embodied interpretation of experiences in time and place and stresses how subjectivity informs the orientation of reflexivity (Lash, 1994). For example, Sharp and Threadgold (2019) have shown how gendered privilege can be ignored by men seeking to assert their feminist credentials-a practice they call "reflexive complicity." In this way, it can be argued that reflexivity needs to be understood in the shared practices of agents involved in knowledge (or ignorance) production (Adkins, 2003).…”
Section: Is Reflexive Modernization the Solution?mentioning
confidence: 99%
“…However, recent literature suggests that there is no guarantee that even reflexive learning will lead to positive outcomes for sustainability. Sharp and Threadgold (2020) introduced the notion of 'reflexive complicity' in their study on gender marginalization, stating that: reflexive complicity is performed when one knows about unequal social relations or forms of marginalization, can observe them and claim to want things to change, but there are no significant changes in practice by the individual and little effort to engage in situational interventions that make a difference (pp. 619-620).…”
Section: Reflexivity In Practice and Researchmentioning
confidence: 99%
“…Seeing their engagement in craft activities through a punk DIY lens allowed participants such as Lindsey and Sam to offer some resistance to such stereotypes. It might be argued then that instead of merely engaging in reflexive complicity (through a more private expression of punk DIY coded as traditionally feminine) they were actually engaging in defiant labour (Sharp & Threadgold, 2020).…”
Section: ‘Do-it-yourself’ or ‘Doing-it-yourself’ (Diy)mentioning
confidence: 99%
“…Indeed Liptrot (2014) found that the punk women in her study were often attracted to punk initially because they saw it as transgressing conventional boundaries of femininity. Research of course has questioned, however, the degree to which such transgression can actually take place within a masculine space such as punk (Leblanc, 2002; Sharp & Threadgold, 2020).…”
Section: Subversionmentioning
confidence: 99%
See 1 more Smart Citation